GAYA KEPEMIMPINAN YANG EFEKTIF DALAM UPAYA MENINGKATKAN PRODUKTIFITAS ANGGOTA POLRESTA BANDAR LAMPUNG - -, Triyono (Jurnal Manajemen Magister Darmajaya, 2016)
The purpose of this research is to know and analyze the effective leadership style in order to increase the productivity of Bandar Lampung Police member. The method used in this study is the method is a qualitative method, with data collection techniques through observation, interview, and documentation while data analysis techniques using data triangulation way. Based on the results of the research, the conclusions are as follows: (1) The leadership style of Kapolresta in improving the productivity of members of Bandar Lampung Police is good and running optimally, it can be seen from several things, among others: (a) Intelligence, the character or the nature of the leadership of Kapolresta Bandar Lampung has the advantage of intelligence, both intellectually and emotionally, (b) Maturity and flexibility of social relationships, in the style of leadership has emotional stability, has extensive social activities, direct supervisors supervise, giving direction directly, appreciating his subordinates and leaders giving freedom to convey his aspirations, (c) Self-motivation and encouragement of achievement, increasing motivation of achievement shown by Kapolresta Bandar Lampung impact on increasing productivity of Bandar Lampung Police (d) relationships, leadership behaviors oriented to relationships are effective enough to improve work productivity. (2) Leadership style factors that inhibit increasing productivity of Bandar Lampung Police members, including (a) expectations and behavior of superiors, (b) characteristics, expectations and subordinate behavior, (c) task requirements, (d) culture and policy organization and (d) expectations and behavior of co-workers.Â Keywords: Leadership Style, Increased Productivity